ISLAMIC-ORIENTED CHARACTER EDUCATION FOR ENVIRONMENTAL SUSTAINABILITY: A CASE STUDY OF PRIMARY SCHOOLS IN BANJARMASIN - Galuh Nashrulloh Kartika MR; Abdul Hafiz; Barsihanor Barsihanor (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
This study explores the implimentation and implications of Islamic-based environmentally sustainable character education in elementary schools in Banjarmasin. Using a qualitative case study approach, the research focuses on principals, teachers, and students as primary subjects. Data were collected through observation, interviews and documentation, with. data analysis involving reduction, presentation, and synthesis for conclusions. To ensure data validity, the study employed technical and source triangulation. Findings indicate that Islamic-based environmentally sustainable character education was facilitated through a series of initiatives: daily reporting, the GPS (Garbage Collection Movement), LISA (see trash pickup) practices, community service actvities, establishement of waste banks, composting, nurseries, hydroponics and TOGA (Medicinal Plant Garden), cultivation,water and energy conservation, innovations in environmentally sustainable behaviors, environmental education programs, formation of Adiwiyata cadres, and guidance for Adiwiyata schools. The implications of this approach for elementary schools in Banjarmasin are reflected in four primary components; the establishment of environmentally conscious school policies, integration of environmentally themes within the curriculum, participatory environmental engagement, and the management of eco-friendly facilities and infrastructure.